Streamlined Yeast Colorimetric Reporter Activity Assays Using Scanners and Plate Readers. (August 2000) - Serebriiskii, Ilya G.; Toby, Garabet G.; Golemis, Erica A.
Two-hybrid systems have become favored tools for detection and analysis of protein interactions because of their low cost and ease of use compared to biochemical or biophysical interaction technologies. It is possible to augment the utility of two-hybrid systems and derivative systems such as dual-bait two-hybrid systems by adapting strategies that speed the analysis of the relative strength of a series of protein-protein associations. This report describes two simple techniques that employ either a flatbed scanner or a plate reader to quantitate the activity of colorimetric reporters such as LacZ or GusA commonly used in two-hybrid approaches.